Pengaruh Gaya Kepemimpinan Terhadap Komitmen Organisasi Melalui Kepuasan Kerja Sebagai Variabel Intervening - Arif Darmawan; Marlinda Aulia Putri (Akuntabilitas, 2017)
This study aims to examine the influence of leadership style on organizational commitment through job satisfaction as intervening variable. This research uses quantitative method with data analysis that is simple regression, path analysis and test of sobel. he results showed that leadership style influence job satisfaction, while job satisfaction affect organizational commitment. The result of path analysis showed that leadership style influence to organizational commitment through job satisfaction as intervening variable. The implications obtained in this study are expected to be used as information for universities to apply good leadership style and pay more attention to job satisfaction from lecturers.